Decreased Serum Oxytocin and Increased Homocysteine in First-Episode Schizophrenia Patients - Liu, Yong; Tao, Huai; Yang, Xiudeng; Huang, Kai; Zhang, Xianghui; Li, Cunyan (Frontiers in Psychiatry, 2019)
Schizophrenia (SZ) is a debilitating and heterogeneous disease. We hypothesized that the oxytocin (OXT) system, inflammation and one-carbon metabolism would have a link with SZ. In this study, serum OXT, OXT receptor (OXTR), interleukin-6 (IL-6), high sensitivity CRP (hsCRP) and homocysteine (Hcy) levels were measured in 52 first-episode schizophrenia (FES) patients and 41 healthy controls (HC) from the Second Xiangya Hospital of Central South University. Meanwhile, the mRNA expressions of OXT and OXTR genes were determined by real-time quantitative PCR. Serum OXT and OXTR levels were significantly lower in FES patients (518.96 ± 22.22 and 174.60 ± 17.11 pg/ml) than the HC group (711.58 ± 40.57 and 252.15 ± 20.62 pg/ml). Serum IL-6 and hsCRP levels showed no difference between the two groups (1.82 ± 0.30 vs. 1.69 ± 0.36 pg/ml, 0.66 (0.22, 1.07) vs. 0.31 (0.13, 0.91) mg/L), but serum Hcy levels were significantly higher in FES patients (20.18 ± 1.83 vs. 15.24 ± 0.82 μmol/ml). The FES patients (0.27 ± 0.02 and 0.20 ± 0.02) have relatively higher mRNA expressions of OXT and OXTR genes than the HC group (0.16 ± 0.01 and 0.14 ± 0.01). In summary, our results suggested the possible function of the OXT system and Hcy in the pathogenesis of SZ.